Teachers' Efforts in Improving the Quality of Islamic Religious Education - Adiyono Adiyono; Widya Pratiwi (Budapest International Research and Critics University, 2021)
Teachers play an important role in helping the development of students to realize their life goals optimally. Islamic religious education teachers in schools are directly related to the achievement of educational goals, especially Islamic religious education in schools. Therefore, Islamic religious education teachers are required to be able to carry out their duties as Islamic religious education teachers not only responsible for delivering subject matter to students, but also being able to shape the personality of students so that in the end students have the main personality. This study uses the pattern and type of qualitative research. Collecting data in this study using observation techniques, interviews, and documentation techniques. For data analysis used descriptive analysis techniques in an effort to make conclusions. The results of this study indicate that, the efforts of teachers in improving the quality of Islamic religious education are divided into three stages. teachers in improving the quality of Islamic religious education related to the profession, by taking S1 PAI education, attending training and education and training training, MGMP and being responsive to the development of the PAI material curriculum, and thirdly, teachers' efforts in improving the quality of Islamic religious education related to the morals of students, namely by connecting each material with morals so that students understand the good and the bad. The benefits of the teacher's efforts in improving the quality of Islamic religious education on the personality of students to the personality of students so that the ability of students increases towards the success of the teaching and learning process of students and can also increase faith and piety in order to increase students' confidence and awareness of the importance of religious knowledge for the life of the world and the hereafter as well as everyday life.